Cursos de formação inicial e continuada e a inserção no mercado de trabalho: o caso da UFSM e das organizações militares de Santa Maria - Macedo, Jonas Carniel de (2015)
Education and work are interrelated rights that the Brazilian citizen acquired along the history of the country and, regarding the current social context, immersed in the globalization and technology, these rights assume an even bigger interdependence. The current study aims at verifying the working market placement of the graduates from the Initial and Continuing Education courses (FIC) carried out by the articulation between Federal University of Santa Maria (UFSM) and the Military Organizations from Santa Maria in the National Program of Access to Technical Education and Employment (PRONATEC) sphere. This research was developed as a study of case in order to diagnose the situation of the graduates considering the working market and the influence of taking the course to reach such objective. The data collection was done through the consultation of documents and records and through questionnaires given to the FIC graduates at Industrial Technical School. The FIC graduates from the years of 2012, 2013 and 2014 were the subjects of this research. The results present a diagnosis of the current situation of FIC courses in terms of effectiveness identifying limitations and suggesting measures that can improve the contribution of these Professional Education courses to place the youth in the working market and encourage them to keep studying.